The Effects of Parents Participation Program and Capacity Building Parents in Nasal Irrigate on the Child Caring Behaviors Among Parents of Pre-school Children with Allergic Respiratory Diseases - กีบาง, จุไรรัตน์ (Journal of The Royal Thai Army Nurses, 2019)
This quasi-experimental research purpose to study effect of Parents Participation Program and Capacity Building Parents in Nasal irrigate on the Child Caring Behaviors Among Parents of Pre-school Children with Allergic Respiratory Diseases. The sample consisted of 51 parents select the sample according to the specifications. The experimental group 26 parents received parents participation program and capacity building parents in nasal irrigate and the control groups 25 parents received regular caring. The instruments used in this study consisted of the parents participation program and capacity building parents in nasal irrigate and the questionnaire on the child caring behaviors among parents of pre-school children with allergic respiratory diseases. Data were analyzed using descriptive statistics, independent t-test and paired t-test. The findings of this study revealed that: 1. The child caring behaviors among parents of pre-school children with allergic respiratory mean score of the parents in the experimental group after participation in the parents participation program and capacity building parents in nasal irrigate was statistically significant higher than the control group (p<.05) 2. The child caring behaviors among parents of pre-school children with allergic respiratory mean score of the parents in the experimental group after participation in the parents participation program and capacity building parents in nasal irrigate was statistically significant higher than their score before participating in the program (p<.05) The results of this study indicate that the parents participation program and capacity building parents in nasal irrigate promote parents to increased the child caring behaviors among parents of pre-school children with allergic respiratory.